Research of methods for water disinfection - Makhonina, O. S.; Shestopalov, O.; Baranova, A. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
Access to safe water remains a challenge in conflict-affected areas. Irregular water supply, which is becoming a common phenomenon, is caused by numerous factors, in particular: 1) wear and tear of water mains that need repair and were damaged as a result of hostilities; 2) reduction in the efficiency of important pumps due to power outages, shelling of power lines that supply energy to the pumps; 3) access problems due to the presence of armed groups, the presence of mines or unexploded shells, as well as the poor condition of roads, which prevent local residents from reaching wells or obtaining water delivered by tankers; 4) problems with access, due to which workers cannot perform repair work or obtain spare parts necessary for repairing water pipes; 5) normative legal acts that limit the freedom of movement and/or supply of goods or water across the contact line, affecting the supply of water from settlements controlled by Ukraine to settlements not controlled by Ukraine; as well as 6) frequent water supply interruptions, which contributed to the deterioration of the situation. In most cases, the use of a combined system can be optimal for high-quality water disinfection. Combined water disinfection is carried out by physical and chemical methods at the same time. Water pollution is determined by its bacteriological examination, which shows the total number of bacteria and the number of indicator bacteria of the coliform group (E. coli) in 1 milligram of water. The main type of bacteria of the Escherichia coli group is E.coli bacteria, which in practice are the easiest to determine and have a high level of resistance coefficient. Traditional methods of water disinfection, namely chlorination and ozonation, are harmful byproducts of disinfection. Ultraviolet radiation is a safe alternative, but quite energy-consuming. The paper analyzes existing methods of decontamination of drinking water, examines the state of the issue, and analyzes alternative methods of decontamination of drinking water.

Доступ до безпечної води залишається проблемою в районах, уражених конфліктом. Нерегулярне водопостачання, яке стає звичним явищем, зумовлене численними факторами, зокрема: 1) зношеністю водогонів, які потребують ремонту та були пошкоджені внаслідок бойових дій; 2) зниження працездатності важливих насосів через перебої з електропостачанням, обстріли електромереж, що постачають енергію насосам; 3) проблеми з доступом через присутність озброєних груп, наявність мін або снарядів, що не розірвалися, а також поганий стан доріг, що не дозволяє місцевим мешканцям дістатися до колодязів або отримати воду, що доставляється автоцистернами; 4) проблеми з доступом, через які працівники не можуть виконувати ремонтні роботи або отримати запчастини, необхідні для ремонту водопроводів; 5) нормативно-правові акти, які обмежують свободу переміщення та/або постачання товарів чи води через лінію зіткнення, що впливає на постачання води з підконтрольних Україні населених пунктів до непідконтрольних їй населених пунктів; а також 6) часті перебої з водопостачанням, що сприяло погіршенню ситуації. У більшості випадків оптимальним для якісного знезараження води може бути використання комбінованої системи. Комбіноване знезараження води здійснюється фізичним і хімічним методами одночасно. Забрудненість води визначається за допомогою її бактеріологічного дослідження, яке показує загальну кількість бактерій та кількість бактерій-індикаторів групи кишкової палички (E. coli) в 1 міліграмі води. Основним видом бактерій групи кишкової палички є бактерії E.coli, які на практиці найлегше визначаються та мають високий рівень коефіцієнта резистентності. Традиційні методи знезараження води, а саме хлорування та озонування, утворюють шкідливі побічні продукти дезінфекції. Ультрафіолетове випромінювання є безпечною альтернативою, проте досить енергозатратною. В роботі проаналізовано існуючі методи знезараження питної води, розглянуто стан питання та проаналізовано альтернативні методи знезараження питної води.
Дослідженя методів знезараження води
Keywords: ozonation; water disinfection; ultraviolet; water purification; озонування; знезараження води; ультрафіолет; очищення води